La introducción de la renta básica en España - Sanzo González, Luis (Cuadernos de Relaciones Laborales, 2006)
As a result of a first experience in the Basque Country, in the 90’s the introduction of programs of income support becomes general in Spain, along the line of the French minimum income for insertion (RMI). Trying to solve the problems entailed by these programs, in the last years some new proposals were outlined. These proposals suggest sustaining the system of income support, more than on traditional welfare benefits, on a universal, individual and unconditional grant. This paper analyses the economic implications of the development of a basic income program in Spain. It concludes with the presentation of a concrete proposal of income support program inspired on the principles of the basic income.